Mathematical Analysis of Fluid Flow through Channels with Slip Boundary - Suharsono, S.; Wu, Yong Hong; Wiwatanapataphee, B. (insipub, 2011)
In this paper, we present analytical solutions for transient flow of Newtonian fluid through micro channels with Navier slip boundary. The derivation of the solutions is based on Fourier series expansion in space. We then investigate the influence of the slip parameters on the phenomena of the transient flow and show the transient pressure field and velocity profile at various instants of time.